Anatomical study of the auditory region of Arctotherium tarijense (Ursidae, Tremarctinae), an extinct short‐faced bear from the Pleistocene of South America. Issue 6 (27th July 2016) - Arnaudo, Maria Eugenia; Bona, Paula; Soibelzon, Leopoldo Hector; Schubert, Blaine W.
Abstract: Here we present the most detailed morphological study of the auditory region of a tremarctinae bear, Arctotherium tarijense Ameghino. In addition, we provide new anatomical information of the Tremarctinae inner ear, such as coplanarity and deviation from orthogonality of the semicircular canals, as an approach to infer the head movements which encountered the extinct forms in locomotion. Based on morphological comparisons, A. tarijense exhibits the following particular features: the cavum tympani presents the highest relative volume compared with other ursids; the processus paraoccipitalis has a foramen that is absent in other tremarctines; there is only one (ventral) recess in the anterior region of the cavum tympani; and the recessus epytimpanicus is the smallest for all ursids studied. In relation to the inner ear, A. tarijense shows the lowest values of orthogonality deviation and highest scores of locomotor agility. Based on this, is possible to make a preliminary proposal that this species had a relative high vestibular sensibility and therefore a better ability to explore different kind of habitats. However, this hypothesis might be contrasted among bears taking into account the orientation of each semicircular canal in a phylogenetic framework.